Asia-Pacific Demand for Military Expenditure: Spatial Panel and SUR Estimates. Issue 4 (7th June 2019) - George, Justin; Hou, Dongfang; Sandler, Todd
Abstract: This article investigates the demand for military expenditure for a sample of key Asia-Pacific countries. Spatial panel demand estimates are presented for three joined spatial units using a fixed-coefficient spatial lag model based on a two-step efficient GMM estimator. Spatial autoregression estimates are next presented for 1991–2015, founded on alternative kinds of country connectivities, such as contiguity, inverse distance, discrete distance, and power-projection considerations. Finally, 11 select countries' demands for defense equations are estimated using seemingly unrelated regressions. From alternative perspectives, these estimated models indicate how Asia-Pacific countries respond to the defense spending of other countries. In the spatial runs, free riding is prevalent despite the growing military might of China, which apparently is not generally viewed as a threat. For the sample period, the projection of Chinese or American power is a relevant spatial factor. The main threat is reflected in non-U.S. allies' reaction to U.S. allies' defense spending during 1991–2015 and to Chinese defense spending after 2002.